P3-5: Temporal Interactions between Binocular Inputs in Visual Evoked-Potentials - Kim, Sunkyue; Lee, Kyoung-Min (i-Perception (London), 2012)
The interaction between neural activity driven by inputs through the two eyes were examined using visual evoked-potentials (VEP) in normal human subjects. VEP recordings were obtained at the occipital electrodes using binocularly asynchronous pattern-reversal checkerboard stimuli: The patter-reversal times for the two eyes differed by 0, ±50, ±150, or ±350 ms, with the positive stimulus-onset asynchrony (SOA) meaning that the right-eye reversal occurred first. For comparison, monocular VEPs were also obtained using trial conditions where the checkerboard pattern-reversals were shown to only one eye, while a blank field to the other. The VEPs of the various trial conditions were analyzed using both temporal and frequency analysis methods. Three observations were made: First, the N75 amplitude was significantly reduced in the ±50 ms SOA conditions. Second, on ±150 ms and ± ms SOA conditions, a negative potential was observed over the period when the stimuli were binocularly incongruent. Third, the alpha-band power was reduced and the beta-band power increased on asynchronous conditions, compared to the synchronous patter-reversal. These findings show that activities of binocular neurons in the visual cortices get modulated by binocular incongruity in the asynchronous pattern-reversal stimuli. Our stimuli may prove valuable in elucidating neural mechanisms of integration of binocular visual inputs, especially when combined with brain source-localization techniques and compared between normal subjects and patients with dysfunction in binocular vision.